Granular Cell Tumor of the Ascending Colon - Samyak Dhruv; Kuldeepsinh P. Atodaria; Dhineshreddy Gurala; Talal El Imad; Jeffrey Abergel (Case Reports in Gastroenterology, 2023)
Granular cell tumor (GCT) was first described by Abrikossoff in 1926. It is a mostly benign tumor with rare malignant transformation. It is defined as a soft tissue neoplasm with abundant eosinophilic cytoplasm. The mean age of diagnosis for GCT is around 45 years. It is rare for GCT to be found in the gastrointestinal (GI) tract. Within the subset of GI tract, the colon is an extremely rare site for it to be found. Franburg-Smith histopathology criteria are used to differentiate a benign from a malignant GCT. The malignant form is aggressive with high recurrence rates after resection. Histopathology and immunohistochemical stains are used to make a definitive diagnosis. Herein, we present a rare case of an ascending colon polyp that was resected and found to be a benign GCT.